2008
DOI: 10.3132/dvdr.2008.010
|View full text |Cite
|
Sign up to set email alerts
|

Patients with the metabolic syndrome and a disturbed cortisol balance display more microalbuminuria

Abstract: T he objective of this study was to investigate whether patients with the metabolic syndrome (MetS) and an imbalance in cortisol metabolism express increased urinary albumin excretion compared to those patients with metabolic syndrome alone.Seventy-four patients with MetS were evaluated using a low-dose dexamethasone suppression test (LDDST) to identify disturbed cortisol balance (cortisol levels > 50 nmol/L after LDDST). The level of albumin in the urine was also evaluated.Disturbed cortisol balance was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…The present study demonstrated a relationship of increased serum cortisol and the presence of microalbuminuria in subjects with T2DM or prediabetes. Previously, a study showed that patients with MetS and disturbed cortisol balance display more microalbuminuria 10 . In patients with T2DM, increased hypothalamic-pituitary-adrenal axis (HPA) activity was found to be related to the presence of some diabetic chronic complications, and the level of cortisol secretion was linked with the number of diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study demonstrated a relationship of increased serum cortisol and the presence of microalbuminuria in subjects with T2DM or prediabetes. Previously, a study showed that patients with MetS and disturbed cortisol balance display more microalbuminuria 10 . In patients with T2DM, increased hypothalamic-pituitary-adrenal axis (HPA) activity was found to be related to the presence of some diabetic chronic complications, and the level of cortisol secretion was linked with the number of diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the traditional cardiometabolic factors, cortisol secretion is also suggested to correlate with renal function in a few studies 9 , 10 . Serum cortisol level was negatively correlated with eGFR levels in patients with essential hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, UAE declined profoundly, independent of changes in blood pressure and plasma glucose levels, in all these patients after amelioration of hypercortisolism [7]. Patients having metabolic syndrome with hypercortisolism displayed more microalbuminuria than did those without hypercortisolism, even though there were no differences in blood pressure, plasma glucose, and serum lipids between the two groups [8]. These clinical evidences indicate that endogenous hypercortisolism caused by enhanced hypothalamic-pituitary-adrenal (HPA) axis activity itself could increase UAE and eventually lead to CKD independent of blood pressure and metabolic factors such as plasma glucose and serum lipids.…”
mentioning
confidence: 94%
“…Microalbuminuria assays are more sensitive to albumin loss in the urine than the common urine dipstick, and urinary protein:creatinine ratio tests can detect protein loss through the urine with lower limits-of-detection than urine dipsticks. Microalbuminuria is used as an indicator in screening for early-stage renal and cardiovascular diseases in humans [ 12 , 14 , 17 , 20 , 21 ]. It is a well-known risk factor associated with deteriorated cardiovascular mortality and diabetic nephropathy in human beings [ 12 - 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%